Surveillance of Shark Species Utilization at the Cilacap Ocean Fishing Port(Indonesia) using a Systems Approach - Priyanto, Nanang; NURANI, TRI WIJI; Solihin, Iin (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
The utilization of shark species in Indonesia still encounters legal violations, thus necessitating an effective surveillance system. This study aims to identify the issues within the surveillance system regarding the utilization of shark species at the Cilacap Ocean Fishing Port (PPS Cilacap). The study uses a system approach, limited to the system analysis stage. The results showed that there are still problems in the shark species utilization monitoring system at PPS Cilacap. These problems result in violations that continue to occur, especially concerning the legal regime of Regional Fisheries Management Organizations (RFMOs). The problems identified in the conclusions of this study cover several aspects. Regarding regulations and institutions, the mandate holders lack synergy, law enforcement remains weak, and support from management institutions for surveillance agencies is insufficient. Regarding surveillance procedures and budget, the existing standard operating procedures (SOPs) do not represent surveillance needs in accordance with legal regulations on shark management, and the available budget is inadequate. Regarding facilities and infrastructure, surveillance facilities for shark species have not been utilized at PPS Cilacap, and unreported fishing still occurs. Regarding human resources, the number of fisheries inspectors does not meet actual needs, while vessel captains and owners’ knowledge and legal awareness remain limited. To address these issues, the recommended strategies include the maintenance and development of port facilities at PPS Cilacap, the integration of information systems among institutions, the dissemination of shark governance, the recruitment, education, and training of fisheries inspectors, the revision of SOPs, and comprehensive law enforcement. Keywords: PPS Cilacap; shark; surveillance system